TWO NEW SPECIES OF PAPHIOPEDILUM (ORCHIDACEAE: CYPRIPEDIOIDEAE) SECTION BARBATA FROM SUMATRA, INDONESIA - Metusala, D. (Edinburgh Journal of Botany, 2017)
Two new species of Paphiopedilum from Sumatra, Indonesia, are described and illustrated. These two species belong in Paphiopedilum section Barbata and are so far known only from Aceh Province in the north of Sumatra.